(ii) Find the volume of the solid obtained by revolving one arc of the cycloid x=a(θ+sinθ)x = a(\theta + \sin \theta) and y=a(1+cosθ)y = a(1 + \cos \theta) about the x-axis.

  1. Parametric Equations: The given parametric equations are:

    x=a(θ+sinθ)x = a(\theta + \sin \theta)

    y=a(1+cosθ)y = a(1 + \cos \theta)

  2. Volume of Revolution:

    The volume V of a solid of revolution about the x-axis using the disk method is given by:

    V=πaby2dxdθdθ V = \pi \int_{a}^{b} y^2 \frac{dx}{d\theta} \, d\theta

  3. Compute dxdθ\frac{dx}{d\theta}:

    First, we need to find dxdθ\frac{dx}{d\theta}:

    x=a(θ+sinθ) x = a(\theta + \sin \theta)

    dxdθ=a(1+cosθ) \frac{dx}{d\theta} = a(1 + \cos \theta)

  4. Square of y:

    Next, we find y2y^2:

    y=a(1+cosθ)y = a(1 + \cos \theta)

    y2=a2(1+cosθ)2y^2 = a^2(1 + \cos \theta)^2

  5. Limits of Integration:

    For one arc of the cycloid, θ\theta ranges from 0 to 2π2\pi.

  6. Set Up the Integral:

    Substitute y2y^2 and dxdθ\frac{dx}{d\theta} into the integral:

    V=π02π[a2(1+cosθ)2][a(1+cosθ)]dθV = \pi \int_{0}^{2\pi} [a^2 (1 + \cos \theta)^2] [a (1 + \cos \theta)] \, d\theta

    V=πa302π(1+cosθ)3dθV = \pi a^3 \int_{0}^{2\pi} (1 + \cos \theta)^3 \, d\theta

  7. Expand and Integrate: Expand (1+cosθ)3(1 + \cos \theta)^3:

    (1+cosθ)3=1+3cosθ+3cos2θ+cos3θ(1 + \cos \theta)^3 = 1 + 3\cos \theta + 3\cos^2 \theta + \cos^3 \theta

    Use the identities cos2θ=1+cos2θ2\cos^2 \theta = \frac{1 + \cos 2\theta}{2} and cos3θ=3cosθ+cos3θ4\cos^3 \theta = \frac{3\cos \theta + \cos 3\theta}{4}:

    (1+cosθ)3=1+3cosθ+3(1+cos2θ2)+(3cosθ+cos3θ4)(1 + \cos \theta)^3 = 1 + 3\cos \theta + 3\left(\frac{1 + \cos 2\theta}{2}\right) + \left(\frac{3\cos \theta + \cos 3\theta}{4}\right)

    Simplify:

    (1+cosθ)3=1+3cosθ+32(1+cos2θ)+34cosθ+14cos3θ(1 + \cos \theta)^3 = 1 + 3\cos \theta + \frac{3}{2}(1 + \cos 2\theta) + \frac{3}{4}\cos \theta + \frac{1}{4}\cos 3\theta

    (1+cosθ)3=52+154cosθ+32cos2θ+14cos3θ(1 + \cos \theta)^3 = \frac{5}{2} + \frac{15}{4}\cos \theta + \frac{3}{2}\cos 2\theta + \frac{1}{4}\cos 3\theta

    Integrate each term:

    02π\int_{0}^{2\pi} \cdot

    (52+154cosθ+32cos2θ+14cos3θ)\left(\frac{5}{2} + \frac{15}{4}\cos \theta + \frac{3}{2}\cos 2\theta + \frac{1}{4}\cos 3\theta\right) \cdot

    dθd\theta

    Since the integrals of cosθ\cos \theta, cos2θ\cos 2\theta, and cos3θ\cos 3\theta over one period are zero, we only need to integrate the constant term:

    02π52dθ=52θ02π=522π=5π\int_{0}^{2\pi} \frac{5}{2} \, d\theta = \frac{5}{2} \theta \Big|_{0}^{2\pi} = \frac{5}{2} \cdot 2\pi = 5\pi

  8. Final Volume:

    V=πa35π=5π2a3V = \pi a^3 \cdot 5\pi = 5\pi^2 a^3

    Thus, the volume of the solid is: 5π2a3\boxed{5\pi^2 a^3}.


SECTION - C

5. (i) In a plane triangle, find the maximum value of cos A cos B cos C.

We have A+B+C=πA + B + C = \pi so that C=π(A+B)C = \pi - (A + B).

cosAcosBcosC=cosAcosBcos[π(A+B)]\cos A \cos B \cos C = \cos A \cos B \cos \left[\pi - (A + B)\right]

=cosAcosBcos(A+B)=f(A,B), say.= -\cos A \cos B \cos (A + B) = f(A, B), \text{ say.}

We get,

fA=cosB[sinAcos(A+B)+\frac{\partial f}{\partial A} = \cos B \left[\sin A \cos (A + B) + \right. \\

cosAsin(A+B)]\left. \\ \cos A \sin (A + B)\right]

=cosBsin(2A+B)= \cos B \sin (2A + B)

and

fB=cosAsin(A+2B)\frac{\partial f}{\partial B} = \cos A \sin (A + 2B)

fA=0,fB=0only when A=B=π/3.\frac{\partial f}{\partial A} = 0, \quad \frac{\partial f}{\partial B} = 0 \quad \text{only when } A = B = \pi/3.

Also

r=2fA2=2cosBcos(2A+B),t=2fB2=2cosAcos(A+2B)r = \frac{\partial^2 f}{\partial A^2} = 2 \cos B \cos (2A + B), \quad t = \frac{\partial^2 f}{\partial B^2} = 2 \cos A \cos (A + 2B)

s=2fAB=sinBsin(2A+B)+cosBcos(2A+B)=cos(2A+2B)s = \frac{\partial^2 f}{\partial A \partial B} = -\sin B \sin (2A + B) + \cos B \cos (2A + B) = \cos (2A + 2B)

When A=B=π/3A = B = \pi/3 , r=1r = -1, s=1/2,t=1s = -1/2, t = -1 so that rts2=3/4rt - s^2 = 3/4.

These show that f(A, B) is maximum for A=B=π/3A = B = \pi/3.

Then C=π(A+B)=π/3C = \pi - (A + B) = \pi/3.

Hence cosAcosBcosC\cos A \cos B \cos C is maximum when each of the angles is π/3\pi/3 i.e., the triangle is equilateral and its maximum value is 1/81/8.

(ii) If u=log(x3+y3+z33xyz)u = \log(x^3 + y^3 + z^3 - 3xyz), show that:

(x+y+z)2u=9(x+y+z)2\left( \frac{\partial}{\partial x} + \frac{\partial}{\partial y} + \frac{\partial}{\partial z} \right)^2 u = \frac{-9}{(x + y + z)^2}

We have,

ux=3x23yzx3+y3+z33xyz,uy=3y23zxx3+y3+z33xyz,uz=3z23xyx3+y3+z33xyz\frac{\partial u}{\partial x} = \frac{3x^2 - 3yz}{x^3 + y^3 + z^3 - 3xyz}, \quad \frac{\partial u}{\partial y} = \frac{3y^2 - 3zx}{x^3 + y^3 + z^3 - 3xyz}, \quad \frac{\partial u}{\partial z} = \frac{3z^2 - 3xy}{x^3 + y^3 + z^3 - 3xyz}

ux+uy+uz=3(x2+y2+z2xyyzzx)x3+y3+z33xyz\therefore \frac{\partial u}{\partial x} + \frac{\partial u}{\partial y} + \frac{\partial u}{\partial z} = \frac{3(x^2 + y^2 + z^2 - xy - yz - zx)}{x^3 + y^3 + z^3 - 3xyz}

=3(x2+y2+z2xyyzzx)(x+y+z)(x2+y2+z2xyyzzx)=3x+y+z= \frac{3(x^2 + y^2 + z^2 - xy - yz - zx)}{(x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx)} = \frac{3}{x + y + z}

Now(x+y+z)2u=(x+y+z)(ux+uy+uz)\text{Now} \quad \left(\frac{\partial}{\partial x} + \frac{\partial}{\partial y} + \frac{\partial}{\partial z}\right)^2 u = \left(\frac{\partial}{\partial x} + \frac{\partial}{\partial y} + \frac{\partial}{\partial z}\right) \left(\frac{\partial u}{\partial x} + \frac{\partial u}{\partial y} + \frac{\partial u}{\partial z}\right)

=(x+y+z)(3x+y+z)= \left(\frac{\partial}{\partial x} + \frac{\partial}{\partial y} + \frac{\partial}{\partial z}\right) \left(\frac{3}{x + y + z}\right)

=3(x+y+z)23(x+y+z)23(x+y+z)2=9(x+y+z)2.= - \frac{3}{(x + y + z)^2} - \frac{3}{(x + y + z)^2} - \frac{3}{(x + y + z)^2} = - \frac{9}{(x + y + z)^2}.

6. (i) If u=xyu = x^y, show that 2ux2y=3uxyz\frac{\partial^2 u}{\partial x^2 \partial y} = \frac{\partial^3 u}{\partial x \partial y \partial z}.

Given:

u=xyu = x^y

We want to show that:

2ux2y=3uxyz\frac{\partial^2 u}{\partial x^2 \partial y} = \frac{\partial^3 u}{\partial x \partial y \partial z}

First, we compute the second partial derivative 2ux2y\frac{\partial^2 u}{\partial x^2 \partial y}:

ux=yxy1\frac{\partial u}{\partial x} = y x^{y-1}

2ux2=y(y1)xy2\frac{\partial^2 u}{\partial x^2} = y (y-1) x^{y-2}

2ux2y=y(y(y1)xy2)\frac{\partial^2 u}{\partial x^2 \partial y} = \frac{\partial}{\partial y} \left( y (y-1) x^{y-2} \right)

Next, we compute the third partial derivative 3uxyz\frac{\partial^3 u}{\partial x \partial y \partial z}:

Since u=xyu = x^y does not depend on z, we have:

3uxyz=z(2uxy)=0\frac{\partial^3 u}{\partial x \partial y \partial z} = \frac{\partial}{\partial z} \left( \frac{\partial^2 u}{\partial x \partial y} \right) = 0

Similarly, for 2ux2y\frac{\partial^2 u}{\partial x^2 \partial y}, we have:

2ux2y=0\frac{\partial^2 u}{\partial x^2 \partial y} = 0

Therefore,

2ux2y=3uxyz\boxed{\frac{\partial^2 u}{\partial x^2 \partial y} = \frac{\partial^3 u}{\partial x \partial y \partial z}}

(ii) Show that the rectangular solid of maximum volume that can be inscribed in a sphere is a cube.

Let 2x, 2y, 2z be the length, breadth, and height of the rectangular solid so that its volume V = 8xyz.

V=8xyz...(i)V = 8xyz \quad \text{...(i)}

Let R be the radius of the sphere so that x2+y2+z2=R2x^2 + y^2 + z^2 = R^2.

F(x,y,z)=8xyz+λ(x2+y2+z2R2)...(ii)F(x, y, z) = 8xyz + \lambda (x^2 + y^2 + z^2 - R^2) \quad \text{...(ii)}

and

Fx=0,Fy=0,Fz=0\frac{\partial F}{\partial x} = 0, \, \frac{\partial F}{\partial y} = 0, \, \frac{\partial F}{\partial z} = 0

give

8yz+2xλ=0,8xz+2yλ=0,8xy+2zλ=08yz + 2x\lambda = 0, \quad 8xz + 2y\lambda = 0, \quad 8xy + 2z\lambda = 0

or

2x2λ=8xyz=2y2λ=2z2λ2x^2\lambda = -8xyz = 2y^2\lambda = 2z^2\lambda

Thus, for a maximum volume x=y=zx = y = z.

i.e., the rectangular solid is a cube.

Go to next page for rest of the questions.

Last updated on -

Page Contents

No Headings